Great Expectations: Microfinance and Poverty Reduction in Asia and Latin America - Heather Montgomery; John Weiss (Asian Development Bank Institute (ADBI), 2005)
Microfinance institutions (MFIs) are often seen by aid practitioners as a manifestly effective means of improving the position of the poor. However, detailed research studies have been much more guarded about their impact. In particular, several studies have raised doubts about the effectiveness of MFIs in reaching the `core poor.' This paper surveys the evidence from Asia and Latin America and contrasts experiences in the two regions. Studies on the former have been carried out more rigorously, but in both regions the evidence that microfinance is reaching the core poor is very limited.
hdl:11540/4168
Keywords: 330; Armutsbekämpfung; Asien; Lateinamerika; Mikrofinanzierung